The role of capping agents in the fabrication of nano-silver-decorated hydrothermal carbons. Issue 5 (October 2019) - Simsir, Hamza; Eltugral, Nurettin; Karagoz, Selhan
Abstract: In this work, silver-decorated hydrothermally grown carbons were fabricated by introducing either silver nitrate, or silver nanoparticles (Ag NPs) which were coated differently with polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), gelatin, and glucose. Hybrid nanostructures were prepared by methods which involve either in situ formation under hydrothermal conditions or mixing of as-prepared hydrothermal carbons (HTCs) with Ag NPs. With these approaches, hybrid nanostructures could be fabricated with some differences in their morphologies. Interestingly, a dense silver core at the center of the HTCs was observed after hydrothermal processing of glucose with gelatin-stabilized Ag NPs while particles were observed to attach to the HTCs surface under mixing conditions. PVP-stabilized Ag NPs were shown to form hybrid products where particles were attached to the surface rather than encapsulated at the center. On the other hand, PVA-stabilized ones were hardly observed on the HTCs upon mixing for 48 h, and they seemed not to produce any hybrid HTC-Ag under hydrothermal processing. Besides, glucose-stabilized Ag NPs were also subjected to the hydrothermal process and HTCs produced with interesting surface characteristics revealed that Ag NPs induce their morphology.